The effects of bodyweight-based exercise with blood flow restriction on isokinetic knee muscular function and thigh circumference in college students - Lee, Kyung Soon; Kim, Hyoung Su; Kang, Dong Yeon; Kim, Young Mi (Journal of Physical Therapy Science, 2015)
[Purpose] The purpose of this study was to investigate the effects of bodyweight-based exercise with blood flow restriction on isokinetic muscular function and thigh circumference in college students. [Subjects and Methods] The subjects were 17 college students who were recruited and randomly assigned to bodyweight-based exercise with blood flow restriction and bodyweight-based exercise groups. Participants performed front lunges and squats at ratings of perceived exertion of 11–13 three times a week during a 6-week training period. The peak torque/ body weight (%) of the knee flexor and extensor was measured using a HUMAC NORM System (Cybex 770-NORM®, Cybex International, Medway, MA, USA), and the circumference of the thigh was measured. PASW Statistics was used for data analysis. [Results] There were significant differences in the peak torque/ body weight (%) of the flexors in both thighs (at 180°/sec) after bodyweight-based exercise with blood flow restriction. In addition, the circumference changes in both thighs were significant after bodyweight-based exercise with blood flow restriction and between the two groups. [Conclusion] This study suggests that bodyweight-based exercise with blood flow restriction may be an effective method to improve the muscle power and hypertrophy of the lower extremity in a clinical setting.